Analisis Kebijakan Pemerintah tentang Pesantren Ramah Anak dalam Upaya Preventif Kekerasan Seksual di Pondok Pesantren - Syarip Hidayatullah Ikromussalam (Fahima, 2023)
The existence of educational institutions is increasingly being scrutinized after the occurrence of several cases of sexual violence in schools, not only that this case spread to Islamic boarding schools which astonished the public through various news media. In response to this problem, the government made regulations through the PPPA minister with the implementation of Child-Friendly Islamic Boarding Schools. This study aims to examine government policies toward child-friendly Islamic boarding schools to prevent sexual violence in Islamic boarding schools. This research is library research with a descriptive analysis approach method to see how far prevention and protection efforts have been carried out. The results of the study show that government regulations and policies in efforts to prevent sexual violence in Islamic boarding schools need to be improved by establishing standardization policies in the management, and implementation of education in Islamic boarding schools and expanding the outreach of socialization in preventing sexual violence in Islamic educational institutions.